stratEst: a software package for strategy frequency estimation - Fabian Dvorak (Journal of the Economic Science Association, 2023)
stratEst is a software package for strategy frequency estimation in the freely available statistical computing environment R (R Development Core Team in R Foundation for Statistical Computing, Vienna, 2022). The package aims at minimizing the start-up costs of running the modern strategy frequency estimation techniques used in experimental economics. Strategy frequency estimation (Stahl and Wilson in J Econ Behav Organ 25: 309–327, 1994; Stahl and Wilson in Games Econ Behav, 10: 218–254, 1995) models the choices of participants in an economic experiment as a finite-mixture of individual decision strategies. The parameters of the model describe the associated behavior of each strategy and its frequency in the data. stratEst provides a convenient and flexible framework for strategy frequency estimation, allowing the user to customize, store and reuse sets of candidate strategies. The package includes useful functions for data processing and simulation, strategy programming, model estimation, parameter testing, model checking, and model selection.
Keywords: C72; C87; C90; 330; Strategy frequency estimation; Software; Repeated games